2012
DOI: 10.1186/1471-230x-12-35
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E COG 133 mimetic peptide improves 5-fluorouracil-induced intestinal mucositis

Abstract: BackgroundIntestinal mucositis is one of the major troublesome side effects of anticancer chemotherapy leading to poor patient compliance. In this study we addressed the role of the novel apolipoprotein E (ApoE) COG 133 mimetic peptide in 5-fluorouracil (5-FU)-challenged Swiss mice and IEC-6 cell monolayers. Experiments were also conducted in C57BL6J ApoE knock-out mice to assess the effects of apoE peptide treatment.MethodsExperimental groups were as follows: unchallenged controls, 5-FU-challenged mice (450 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 41 publications
(52 reference statements)
5
22
0
Order By: Relevance
“…Neutrophil infiltration has been reported in several studies that assessed mucositis (24,32,33). We observed intermediate MPO activity in animals receiving L-arginine.…”
Section: Discussionsupporting
confidence: 45%
“…Neutrophil infiltration has been reported in several studies that assessed mucositis (24,32,33). We observed intermediate MPO activity in animals receiving L-arginine.…”
Section: Discussionsupporting
confidence: 45%
“…We have also confirmed a healing effect of the apoE COG133 in the rat jejunal IEC-6 wound model after 5-FU exposure (15). Ala-Gln is a glutamine compound with increased solubility and stability.…”
Section: Discussionsupporting
confidence: 72%
“…In a study by Singh et al (62), the group further demonstrated the protective efficacy of ApoE mimetic peptide COG112 in inhibiting inflammatory responses in murine models of Citrobacter rodentium- induced and DSS-induced colitis. In other studies with mice, the ApoE mimetic peptide COG133 was shown to be equally protective against 5-fluorouracil-induced intestinal mucositis (63) and mitigating the inflammatory response to LPS challenge (64). In this regard, our present findings further highlights the importance of ApoE in maintaining gut homeostasis and that perhaps ApoE mimetic peptides would present a potential therapeutics to correct ApoE deficiency-associated microbiotal dysbiosis that predisposes colitis.…”
Section: Discussionmentioning
confidence: 93%